2019
DOI: 10.1590/s0102-053620190314
|View full text |Cite
|
Sign up to set email alerts
|

Prospection of genetic resistance resources to root-knot nematodes in cucurbit genotypes

Abstract: The aim of this research was to prospect genetic resistant sources to root-knot-nematode in Cucurbitaceae accessions. Two assays were conducted, the first to evaluate the resistance to root-knot nematode, M. incognita race 1 in accessions of Lagenaria vulgaris; Sicana odorifera; Cucurbita facifolia; Luffa sp.; Citrullus lanatus cv. Citroides; Lagenaria vulgaris; Cucurbita moschata; Cucurbita moschata x Cucurbita maxima; Cucumis melo and Cucumis metuliferus. The second to evaluate the reaction to nematode M. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The main objective of this study was to determine host suitability of C. metuliferus BGV11135 and C. amarus BGV5167 for the nematodes M. chitwoodi, M. enterolobii and M. luci, to provide insights into the potential use of these rootstocks for melon and watermelon crops, and to provide this information to assist management of RKN species. Previous studies have reported resistance of some C. metuliferus accessions to M. incognita, M. arenaria, M. hapla, M. javanica and M. enterolobii (Walters et al, 2006;Ye et al, 2017;Pinheiro et al, 2019), and that of C. amarus to M. arenaria, M. enterolobii, M. incognita and M. javanica (García-Mendívil et al, 2019;Waldo et al, 2023). The present paper is the first report on levels of resistance of C. metuliferus and C. amarus to M. chitwoodi and M. luci.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main objective of this study was to determine host suitability of C. metuliferus BGV11135 and C. amarus BGV5167 for the nematodes M. chitwoodi, M. enterolobii and M. luci, to provide insights into the potential use of these rootstocks for melon and watermelon crops, and to provide this information to assist management of RKN species. Previous studies have reported resistance of some C. metuliferus accessions to M. incognita, M. arenaria, M. hapla, M. javanica and M. enterolobii (Walters et al, 2006;Ye et al, 2017;Pinheiro et al, 2019), and that of C. amarus to M. arenaria, M. enterolobii, M. incognita and M. javanica (García-Mendívil et al, 2019;Waldo et al, 2023). The present paper is the first report on levels of resistance of C. metuliferus and C. amarus to M. chitwoodi and M. luci.…”
Section: Discussionmentioning
confidence: 98%
“…In cucurbits, the experimental melon rootstocks Cucumis metuliferus BGV11135 display resistance to M. arenaria, M. incognita and M. javanica (Expósito et al, 2018, and, as well as Citrullus amarus, a commercial watermelon rootstock (García-Mendívil et al, 2019;Waldo et al, 2023). Additionally, three accessions of C. metuliferus 'Kino' exhibit resistance to M. enterolobii, M. incognita race 1, and M. javanica (Pinheiro et al, 2019). Waldo et al (2023) also evaluated 108 different accessions of C. amarus, and some of these were resistant to M. enterolobii.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbites in general have morpho-agronomic characteristics that make it possible to use them in a variety of ways, whether in feeding or culture management when used as a rootstock (CHAUDHARI et al, 2017;PINHEIRO et al, 2019;SANTOS et al, 2020;ZHOU et al, 2014).Grafting has been very sought after for cucurbits in the management of diseases, including charcoal rot (COHEN; ELKABETZ; EDELSTEIN, 2016), caused by Macrophomina phaseolina (Tassi) Goid. (1947), which affects several economically important crops of the family, such as melon and watermelon (MEDEIROS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Además, el proceso de infección del sistema radicular contribuye a la entrada de otros fitopatógenos que predisponen a la planta a estrés ambiental perjudicando su desarrollo (Marino et al, 2012;Andrade et al, 2016), y causante de importantes pérdidas económicas en cultivos de climas tropicales y subtropicales (López-Gómez et al, 2015;Sikora et al, 2018), así como en cultivos conducidos en sistemas de invernadero o bajo protección de temperaturas inclementes (Nyczepir, 2013). Se reconoce que la presencia de Meloidogyne es el mayor factor limitante para la producción de cucurbitáceas en el mundo (Pinheiro et al, 2019;Ito et al, 2014).…”
Section: Introductionunclassified